Prevalence of Candida spp. associated with bacteria species on complete dentures - Ribeiro, Daniela G.; Pavarina, Ana Claudia [UNESP]; Dovigo, Lívia Nordi [UNESP]; Machado, Ana Lucia [UNESP]; Giampaolo, Eunice T.; Vergani, Carlos Eduardo [UNESP] (Wiley-Blackwell, 2012)
Prevalence of Candida spp. associated with bacteria species on complete denturesObjective: This study evaluated the prevalence of Candida spp., Streptococcus mutans and Staphylococcus aureus isolated from complete upper dentures.Background: Factors that may increase the number of microorganisms in the oral cavity include denture-wearing and deficient denture hygiene.Materials and Methods: Ninety denture wearers participated in this study. Collection of biological material from each denture was performed on all denture surfaces. Conventional biochemical methods were used to identify the microorganisms. Descriptive statistical analysis was performed on percentage data.Results: Candida spp. were the most frequent microorganisms found on dentures (65.5%), while Strep. mutans and Staph. aureus were present in 53.3 and 34.4%, respectively.Conclusion: Candida species were the most frequent microorganisms on dentures, followed by Strep. mutans and Staph. aureus.
Keywords: complete denture; prevalence; Candida; Streptococcus mutans; Staphylococcus aureus